الجمالية بين تعدد الرؤى واختلاف المفاهيم: Aesthetic between multiple visions and different concepts - El Marrakchi, Hanan Mohamed (SIBAWAYH Arabic Language and Education, 2023)
شكل الجمال محورا أساسيا في النظر الفلسفي العام الذي يشمل المعرفة والوجود والأخلاق، إذلم يكن ممكنا تجاوز الاهتمام الجمالي لإقامة نسق فلسفي متكامل، ذلك أن الجمال حاضر باستمرار ضمن التصور العام الذي يبرر تداخل مبدأ الوجود بنظرية المعرفة بالتصور الأخلاقي. وكثيرة هي الكتب والفلسفات التي درست موضوع الجمال منذ ما قبل أفلاطون وأرسطو في العصر اليوناني وحتى كروتشه والوجوديين والاتجاه الرمزي في العصر الحديث، وقد عنيت هذه الكتب بتناقل الأفكار الأساسية ومقولاتها في علم الجمال، مع بعض فروق وميزات بين هذه الفلسفة أو تلك.ويبقى موضوع الجمال من المواضيع التي تطرح إشكالات تدور حولها آراء وأفكار عديدة، يتفق بعضها ويختلف بعضها الآخر، إذ يصعب تأطيره وتحديد جوهره وكذا الإلمام بكل جوانبه. هذا ما سنحاول الوقوف عنده من خلال هذا البحث.Beauty formed an essential axis in the general philosophical view that includes knowledge, existence, and ethics. It was not possible to go beyond the aesthetic interest to establish an integrated philosophical system, because beauty is constantly present within the general perception, which justifies the overlap of the principle of existence with the theory of knowledge with the moral perception, and there are many books and philosophies that have studied the subject of beauty. From before Plato and Aristotle in the Greek era until Croce, the existentialists, and the symbolic trend in the modern era, these books were concerned with transmitting the basic ideas and their categories in aesthetics, with some differences and features between this or that philosophy.The topic of beauty remains one of the topics that raises problems around which many opinions and ideas revolve, some of which agree and others differ, as it is difficult to frame it and determine its essence, as well as to be familiar with all its aspects. This is what we will try to find out through this research. Keywords: beauty - aesthetics - art - philosophy - literature